Diurnal Variation of Short-Term Repetitive Maximal Performance and Psychological Variables in Elite Judo Athletes - Chtourou, Hamdi; Engel, Florian Azad; Fakhfakh, Hassen; Fakhfakh, Hazem; Hammouda, Omar; Ammar, Achraf; Trabelsi, Khaled; Souissi, Nizar; Sperlich, Billy (Frontiers in Physiology, 2018)
Objectives: The aim of this study was to examine the effect of time of day on short-term repetitive maximal performance and psychological variables in elite judo athletes. Methods: Fourteen Tunisian elite male judokas (age: 21±1 years, height:172±7 cm, body-mass: 70.0±8.1 kg) performed a repeated shuttle sprint and jump ability (RSSJA) test (6×2×12.5 m every 25-s incorporating one countermovement jump (CMJ) between sprints) in the morning (7:00 a.m.) and afternoon (5:00 p.m.). Psychological variables (Profile of mood states (POMS-f) and Hooper questionnaires) were assessed before and ratings of perceived exertion (RPE) immediately after the RSSJA. Results: Sprint times (p>0.05) of the six repetition, fatigue index of sprints (p>0.05) as well as mean (p>0.05) jump height and fatigue index (p>0.05) of CMJ did not differ between morning and afternoon. No differences were observed between the two times-of-day for anxiety, anger, confusion, depression, fatigue, interpersonal relationship, sleep and muscle soreness (p>0.05). Jump height in CMJ 3 and 4 (p<0.05) and RPE (p<0.05) and vigor (p<0.01) scores were higher in the afternoon compared to the morning. Stress was higher in the morning compared to the afternoon (p<0.01). Conclusion: In contrast to previous research, repeated sprint running performance and mood states of the tested elite athletes showed no-strong dependency of time-of-day of testing. A possible explanation can be the habituation of the judo athletes to work out early in the morning.